A review on personalized medicine technique using cognitive computing - Jayanthi, Appawala; Ramu, Gandikota; Rani, K. Pushpa (International Journal of Engineering and Technology, 2018)
Personalized Medicine is an important strategy for disease diagnosis and pre-care. This approach considers his/her personal data, circumstances, and genes to cure the disease. This method allows physicians and researchers to prognosticate the medication and prevent policies for appropriate viruses. The concept of cognitive computing works like a human brain to analyze and process the data. This method includes an automated system for using natural language processing, pattern recognition, and data mining to simulate how the human brain works. In this review, the synthesized overview of the current status of research on personalized medicine and how to address personalized medicine, using cognitive computing, are discussed. In addition, the national and international status of the research and issues, regarding personalized medicine, are presented.